Effect of Irrigation Strategies on Yield of Drip Irrigated Sunflower Oil and Fatty Acid Composition and its Economic Returns - Semih Metin Sezen; Dilşat Bozdoğan Konuşkan; Servet Tekin (Journal of Agricultural Sciences)
A field trial was conducted to observe the effects of different irrigation strategies on the yield and the water use, oil content and marginal return of sunflower which was irrigated by means of a drip system during 2010 and 2011 under Çukurova condition of Turkey. The irrigation strategies include three irrigation intervals (A1: 25 mm; A2: 50 mm; A3: 75 mm of cumulative pan evaporation) and six water levels (WL) based upon the percentages of cumulative pan evaporation (WL1= 0.50, WL2= 0.75, WL3= 1.00 and WL4= 1.25). In addition, WL5= PRD50 and WL6= PRD75 treatments were evaluated. They obtained water from alternative laterals 50% and 75% of the WL3 treatment. Additionally, a nonirrigated treatment (NI) was included as control plot in the experiment. In each of the experimental years, the largest and the smallest average yields were acquired from the A2WL4 and NI treatments, respectively. The oil content and fatty acid composition were significantly affected by irrigation strategies. The oil content increased with the increasing amount of irrigation. Among all irrigation intervals, PRD-50 (WL5) treatment provided the largest water use efficiency (WUE) and irrigation water use efficiency (IWUE) values in both growing seasons. In order to attain higher yields and a generated the marginal return, A2WL4 irrigation regime is suggested for sunflower production in the Mediterranean region. A2WL3 water strategy is proposed for an acceptable marginal return in case of water shortage.